The relationship between working alliance and symptom improvement in cognitive therapy for posttraumatic stress disorder - Beierl, E; Murray, H; Wiedemann, M; Warnock-Parkes, E; Wild, J; Stott, R; Grey, N; Clark, DM; Ehlers, A (Frontiers Media, 2021)
Background: Working alliance has been shown to predict outcome of psychological treatments in multiple studies. Conversely, changes in outcome scores have also been found to predict working alliance ratings.